Relevance of the Second Harmonic Generation to Characterize Crystalline Samples. Issue 6 (8th May 2015) - Simon, Florent; Clevers, Simon; Dupray, Valérie; Coquerel, Gérard; Coquerel, Gerard; Couvrat, Nicolas; Cartigny, Yohann
Abstract The application of powder second harmonic generation (P‐SHG), temperature‐resolved SHG (TR‐SHG), and SHG microscopy (SHGM) in the characterization of bulk crystalline samples is illustrated. P‐SHG applied to powder samples can be an extremely sensitive approach to detect the absence of an inversion center in crystalline structures, TR‐SHG serves to monitor temperature‐induced phase transitions, and SHGM is used in the detection of non‐centrosymmetric zones inside a heterogeneous material. These methods are of great relevance, e.g., in the pharmaceutical industry where crystalline active pharmaceutical ingredients are often made of a single enantiomer and are therefore non‐centrosymmetric. Herein, several examples are provided to describe how a given SHG signal should be interpreted. A general procedure to carry out a P‐SHG experiment is illustrated in detail.